2013
DOI: 10.1590/0074-0276108062013014
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of Culex quinquefasciatus (Diptera: Culicidae) larval habitats at ground level and temporal fluctuations of larval abundance in Córdoba, Argentina

Abstract: The aims of this study were to characterise the ground-level larval habitats of the mosquito Culex quinquefasciatus, to determine the relationships between habitat characteristics and larval abundance and to examine seasonal larval-stage variations in Córdoba city. Every two weeks for two years, 15 larval habitats (natural and artificial water bodies, including shallow wells, drains, retention ponds, canals and ditches) were visited and sampled for larval mosquitoes. Data regarding the water depth, temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Bionomic data. This species develops mainly in artificial breeding sites, such as ditches, sewers and pools with superficial water (Stein et al 2011(Stein et al , 2016bGrech et al 2013). Nevertheless, Almirón and Brewer (1996) reported collections in natural habitats with aquatic vegetation.…”
Section: Resultsmentioning
confidence: 99%
“…Bionomic data. This species develops mainly in artificial breeding sites, such as ditches, sewers and pools with superficial water (Stein et al 2011(Stein et al , 2016bGrech et al 2013). Nevertheless, Almirón and Brewer (1996) reported collections in natural habitats with aquatic vegetation.…”
Section: Resultsmentioning
confidence: 99%
“…Positive associations were observed between Culex species larval abundance and pH, with pH values ranging between 6.8–8.5 [10], 6.4–8.2 [60] and 7.3–11.4 [61]. However, other authors reported negative associations [62], or no relationship between this variable and immature Culex [7, 8, 11]. Conductivity and DO are two of the most useful and commonly measured water quality parameters.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement, Cx. apicinus was collected less frequently from natural breeding sites including pools, spring and creek tributaries [7, 29]. In this study, Cx.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This association occurs because the characteristics of swamps with aquatic plants can be used as breeding grounds and increase the number of mosquitoes. Culex quinquefasciatus mosquito larvae are found to be highest in permanent water habitats such as swamps with aquatic vegetation especially in summer (Grech et al, 2013).…”
Section: Vulnerability Of the Area In Terms Of Water Puddle Existencementioning
confidence: 99%